Cracking the Code: Financial Performance Factors in Food and Beverage Companies - Nathania Djohari; Meutia Riany (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
This research investigates the relationship between company size, institutional ownership, and dividend policy, and their effect on the financial performance of food and beverage companies traded on the IDX period 2019-2023. This research is driven by the need to explain the relationship between dividend policy, institutional ownership, company size, and financial performance, especially in the context of the food and beverage industry, as it has unique business dynamics. This research adopts a purposive sampling technique and applies multiple linear regression analysis, as the hypotheses are tested through a t-test. With fifty firm-year observations, this research indicates that institutional ownership exerts a positive impact on financial performance. In addition, the dividend policy and firm size do not have a significant impact on the company's financial performance. The findings of this research can assist decision-makers in designing policies that align with the characteristics of the industrial sector and enhance the understanding of factors influencing the company’s financial performance.